Satisfacción laboral de los trabajadores en la Bananera La Mil - Nivela Bonoso, Diana Carolina (2021)
The main objective of the research work was to analyze the job satisfaction of the La Mil Banana workers and the main components that influence the study variable, through descriptive methodology and the implementation of technical instruments that allowed obtaining relevant and timely information to reach the conclusions of the research work; an interview was conducted with the farm administration, in addition, with the use of a questionnaire on job satisfaction, a survey was conducted with 54 agricultural workers how work in said banana plantation under study, in whose results they stated that they feel dissatisfied with the remuneration that the perceive, the working hours are unstable, the working conditions grow from an optimal adaptation, among other factors. In the development of this case study, the activities carried out by the La Mil Banana are detailed, the problematic situations that arise in said family business are explained and the theme in reinforced with relevant definitions that help to have a clearer and more argumentative vision about investigative activity. It is fir and necessary to mention that in the development of this work, tables ore presented that reflect the results of the application of the information collection instruments, which include the respective analysis and interpretation of the data obtained. In conclusion, it was show that the degrees of satisfaction of the workers of the La Mil Banana are conditioned by the dissatisfaction with the payment of their work, instable working hours, monotony of work, and unfavorable working conditions for the good performance of the workers.